Діагностичне значення ЕКГ-індексів у дітей з двостулковим аортальним клапаном серця - Каменщик, Андрій Володимирович; Kamenshchyk, A.; Каменщик, А. В. (Сумський державний університет, 2018)
Метою роботи стало визначення діагностичного значення ЕКГіндексів Соколова–Лайона (ІСЛ) й Корнельського вольтажного індексу (КВІ), а також тривалості систоли (ТС) й висоти зубця R у відведенні avl (Ravl) у 47 дітей з встановленим за даними допплерехокардіографії двостулковим аортальним клапаном серця (ДАК). В результаті дослідження було встановлено, що у дітей з ДАК порівняно із 44 дітьми групи контролю має місце достовірне збільшення ІСЛ, ТС, R aVL та тенденція до збільшення КВІ. При проведенні кореляційного аналізу у дітей з ДАК на відміну від групи контролю встановлено наявність взаємозв’язків між ІСЛ та товщиною задньої стінки лівого шлуночка та міжпередсердної перетинки, ударним об’ємом лівого шлуночка, у той час як КВІ мав взаємозв’язки з розмірами правого шлуночка та волюметричними показниками клапана легеневої артерії, а Ravl з градієнтом тиску на аортальному клапані. За даними ROC-аналізу у дітей з ДАК виявлене найбільше предикативне значення щодо розвитку гіпертрофії міокарду ІСЛ більшого за 30 mV та R aVL більшого за 9 mV щодо збільшення градієнту тиску на аортальному клапані. Отримані дані можуть бути використані для визначення ризиків розвитку серцевих ускладнень у дітей з ДАК.Introduction: The bicuspid aortic valve (BAD) is one of the most widespread congenital heart anomalies. The disease in many cases has asymptomatic course with later consequences beyond the pediatric age as a severe heart complications, sudden death and dissection of aorta. In addition, the ECG patterns remain unchanged to the time of aortal stenosis development and the signs of myocardial hypertrophy take place only in 30 % of children. Purpose of the study: Detection of Sokolow–Lyon and Cornell ECG-indexes, as well as systolic lengthening and R wave height in aVL lead with establishing of their diagnostic values in children with bicuspid aortic valve. Materials and methods: The study was conducted in 47 children with BAV diagnosed by doppler echocardiography, not having the signs of heart failure and in 44 healthy children of control group. The values of Sokolow–Lyon and Cornell voltage indexes, systolic lengthening and R wave height in avl lead were detected. Cardiographic hypertrophic Sokolow–Lyon Index (SLI) was calculated as the sum of bioelectric potentials of the S1 wave and the maximal R5 or R6 waves (mV) in the thoracic leads. The obtained data were processed statistically with Statistica 6.0 program using the Student’s test, quartile assessment, correlations and ROC-analysis. Discussion: In children with BAV compared to control group the significant increasing of SLI, RaVL, SL values and tendency to CVI values increasing were detected. The correlation analysis revealed positive interrelations of the values of SLI with the left ventricle posterior wall depth and the ventricular septum depth and negative ones with the ejection fraction in children with BAV. At the same time, CVI had positive correlation with the systolic volume and the right ventricle transversal dimension, and, negative interrelation with the pulmonary artery valve velocity. RaVL had a fairly strong correlation with the pressure gradient at the aortic valve, and negative interrelation with left ventricle posterior wall depth and the ventricular septum depth. It should also be noted that the SL had no significant correlations with the volumetric Doppler echocardiography parameters at the aortic valve and with the left ventricle posterior wall depth and ventricular septum depth. It was established that in children with BAV the most predictive value for the development of further left ventricle myocardial hypertrophy which is detected by Doppler echocardiography has the Sokolow–Lyon index exceeding 30 mV as well as the height of the R wave in the aVL lead more than 9 mV may serve as predictor of an increase pressure gradient at aortic valve. The obtained data testifies about the development of disadaptive functional changes and disorders of contractile activity of the left ventricle in the early stages of myocardial hypertrophy development in children with BAV and could be used to stratify the risk of further cardiac complications. Целью работы стало определение диагностического значения ЭКГ индексов Соколова–Лайона (ИСЛ) и Корнельского вольтажного индекса (КВИ), а также продолжительности систолы (ПС) и высоты зубца R в отведении aVL (R avVL) у 47 детей с установленным по данным допплерэхокардиографии двустворчатым аортальным клапаном сердца (ДАК). В результате исследования было установлено, что у детей с ДАК по сравнению с 44 детьми группы контроля имеет место достоверное увеличение ИСЛ, ТС, R aVL и тенденция к увеличению КВИ. При проведении корреляционного анализа у детей с ДАК в отличие от группы контроля установлено наличие взаимосвязей между ИСЛ и толщиной задней стенки левого желудочка и межпредсердной перегородки, ударным объемом левого желудочка, в то время как КВИ имел взаимосвязи с размерами правого желудочка и волюметрическими показателям клапана легочной артерии, а R aVL с градиентом давления на аортальном клапане. По данным ROC-анализа у детей с ДАК обнаружено наибольше предикативное значение с точки зрения развития гипертрофии миокарда ИСЛ превышающего 30 mV и R aVL выше 9 mV с точки зрения увеличения градиента давления на аортальном клапане. Полученные данные могут быть использованы для определения рисков развития сердечных осложнений у детей с ДАК.
Diagnostic value of ECG-indexes in children with bicuspid aortic valve
Диагностическое значение ЭКГ-индексов у детей с двустворчатым аортальным клапаном сердца
Keywords: індекс Соколова–Лайона; Корнельський вольтажний індекс; діти; допплерехокардіографія; двостулковий аортальний клапан; ROC-аналіз; Sokolow–Lyon index; Cornell voltage index; children; Doppler-echocardiography; bicuspid aortic valve; ROC-analysis; индекс Соколова–Лайона; Корнельский вольтажный индекс; дети; допллерехокардиография; двухстворчатый аортальный клапан; ROC-анализ